Growth of Aluminium Nitride Thin Film using Pulse-Modulated Rf Magnetron Sputtering Plasma - Tahan, M.; Nafarizal, N.; Sahdan, M. Z.; Bakri, A. S.; Raship, N. A.; Ahmad, M. K.; Soon, C. F.; Ahmad, M. Y. (International Journal of Integrated Engineering, 2020)
Aluminum nitride (AlN) thin films on silicon (Si) (100) substrates are grown by pulsed rf magnetron sputtering at constant power 200 W, 50 % duty cycle, and substrate at room temperature. The films were characterized using filmetrics, X-ray diffraction, energy dispersive spectroscopy (EDS) and atomic force microscopy (AFM) techniques. The deposited AlN thickness using frequency of 5 Hz for distance of 1-inch and 6-inches were 70.74 nm and 20.40 nm, respectively. The depositions rate is obviously affected by the working distance between the target to the substrates. This is because, at shorter distance between target to substrate, the kinetic energy of bombardment particles become higher. Thus, higher deposition rate and good crystallinity can be obtained as the Al atom and N atom will deposited directly to the substrates. Then, the effect of pulse frequency was investigated.  The thickness of AlN thin films using frequency of 5 Hz, 3 Hz and 1 Hz is 70.74 nm 63.72 nm, and 70.23 nm, respectively. The effects of frequency using pulsed rf magnetron was significantly small. The experimental results clearly demonstrate that the energy supplied to the plasma significantly influence the stoichiometric and crystallisation of the thin films.